Loss of native rocky reef biodiversity in Australian metropolitan embayments. Issue 1 (15th June 2015) - Stuart-Smith, Rick D.; Edgar, Graham J.; Stuart-Smith, Jemina F.; Barrett, Neville S.; Fowles, Amelia E.; Hill, Nicole A.; Cooper, Antonia T.; Myers, Andrew P.; Oh, Elizabeth S.; Pocklington, Jacqui B.; Thomson, Russell J.
Highlights: Rocky reef biodiversity is described along three urban pollution gradients. Fish and invertebrate richness and productivity declines on impacted reefs. Invasive species dominate sites close to city ports. Smaller, faster growing species predominate in the most highly impacted areas. Abstract: Urbanisation of the coastal zone represents a key threat to marine biodiversity, including rocky reef communities which often possess disproportionate ecological, recreational and commercial importance. The nature and magnitude of local urban impacts on reef biodiversity near three Australian capital cities were quantified using visual census methods. The most impacted reefs in urbanised embayments were consistently characterised by smaller, faster growing species, reduced fish biomass and richness, and reduced mobile invertebrate abundance and richness. Reef faunal distribution varied significantly with heavy metals, local population density, and proximity to city ports, while native fish and invertebrate communities were most depauperate in locations where invasive species were abundant. Our study adds impetus for improved urban planning and pollution management practises, while also highlighting the potential for skilled volunteers to improve the tracking of changes in marine biodiversity values and the effectiveness of management intervention.